Characterization of Root Surface and Endorhizosphere Pseudomonads in Relation to Their Colonization of Roots - van Peer, Ron (1990)
An extensive colonization of the endorhizosphere by fluorescent pseudomonads was observed in tomato plants grown on artificial substrates. These studies reveal that a significantly higher percentage of pseudomonads obtained from the endorhizosphere (30%) reduced plant growth than those obtained from the root surface (4%). Lipopolysaccharide patterns, cell envelope protein patterns, and other biochemical characteristics indicated that Pseudomonas isolates obtained from the endorhizosphere are distinct from Pseudomonas isolates obtained from the root surface. Isolates from the endorhizosphere especially were able to recolonize the endorhizosphere of both sterile and nonsterile tomato roots. The ability of the endorhizosphere isolates to colonize the endorhizosphere significantly correlated with their agglutination by tomato root agglutinin but did not correlate with chemotaxis to seed exudates of tomato. No correlation between colonization of the endorhizosphere and agglutination by root agglutinin could be demonstrated for the root surface isolates. We propose that agglutination of specific Pseudomonas strains by root agglutinin is of importance in the initial phase of adherence of bacteria to the root surface.